Consumer Perspective On Osyin Glow Marketed Through Tiktok Shop - Kurniawan, Rizky; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2025)
The purpose of the study: this study aims to find out how consumers view Osyin Glow products marketed through TikTok Shop, including their perception of product quality, price, and value. Design/Method/Approach: This study applies a qualitative method with a phenomenological approach, using thematic analysis techniques. This collection was carried out using triangulation techniques, which involved interviews with two customers on the TikTok Shop Osyin Glow account who had shopping experience and were willing to be interviewed. The selection of informants meets the requirements of relevance, recommendation, relationship, readiness, and assurance. The validity is tested by triangulation techniques. Research Findings: Research shows that the quality of Osyin Glow products has a significant positive effect on consumer buying interest on TikTok Shop. Consumers tend to be more interested in buying products that they consider to be of good quality. Theoretical contribution/Originality: This research has originality because it focuses on a specific product, namely Osyin Glow, which is marketed through TikTok Shop. This provides a new perspective in understanding how beauty products compete in a highly competitive digital market. Practitioner/Policy Implications: This research that TikTok Shop Osyin Glow improves customer satisfaction, it is important for Osyin Glow to ensure good service quality, including quick response to consumer inquiries and complaints, as well as ease in the purchase process. Research limitations: these limitations suggest that while the research provides valuable insights into consumers' perspectives on Osyin Glow on TikTok Shop, there are several aspects that need to be considered for future research in order for the results to be more comprehensive and representative.